POTENTIAL USE OF WATERGUARD AS A DISINFECTANT FOR DOMESTIC WATER USE - Yohana, L; Mashauri, D. A (Tanzania Journal of Engineering and Technology, 2018)
Water Guard which consists of 0.75% sodium hypochlorite (chlorine-based water disinfectant solution) has been identified as an alternative method for treatment of domestic drinking water. The aim of this study was to investigate the effectiveness of Water Guard in disinfecting drinking water from different sources drawn from Kinondoni district, Dar es Salaam as well as to establish appropriate dosage that can be used during the treatment. Results showed that, a dose of 4.0mL per 20 litrer of water guard is sufficient for disinfection of urban water sources. The above prescribed doses provide 100% disinfection efficiency with residue chlorine of less than 0.3mg/l. Water with turbidity values of 30-35 NTU, chlorine dosage of 8mL/20 litres is recommended and this gives residue chlorine of 0.3 €“ 0.5 mg/L. From this study, it can be concluded that, Water guard is effective against pathogen and that there is an increase of residue chlorine as the dosage increases irrespective of from which source the water was drawn. Also the safety of water is obtained even where the residual chlorine is less that 0.1mg/l. However, there are health implications associated with the use of Water Guard which need further research